DESAIN SISTEM PEMBELAJARAN JARAK JAUH BERBASIS SMART CLASSROOM MENGGUNAKAN LAYANAN LIVE VIDEO WEBCASTING - Yasdinul Huda; Delsina Faiza (Universitas Negeri Padang, 2019)
The research aims to provide broad access to education for people in the Industrial Revolution 4.0 through various higher education institutions that actively participate using the Blended Learning model. The long-term goal of this research is to develop innovative and flexible learning models based on Smart Classroom. System design in this study was developed to realize a balance between virtual teaching (virtual class) and face-to-face (physical class) that takes place at the same time using the Live Video Webcasting service. The research method uses a quantitative approach and the type of research is R & D adopting the Thiagarajan 4D development model. This research produces a Smart Classroom system based on Streaming Webcast through several stages, namely: (1) System Design, (2) System Creation, (3) System Testing. This developed system allows interaction in learning in the physical class as well as teaching in a virtual class remotely.Keywords: Revolusi Industri 4.0, Blended Learning, Smart Classroom, Live Video Webcasting.